Skin temperature contribution to the decrease in withdrawal latency following chronic constriction injury - Voděrová, Lucia; Šandera, Štěpán; Drobil, Tomáš; Plevová, Barbora; Vaculín, Šimon (Physiology & behavior, 2020)
BACKGROUND: Chronic constriction injury (CCI) is widely used as an animal neuropathic pain model. Neuropathic pain is considered to exist when withdrawal latency to thermal stimulation is decreased after inducing a CCI to the sciatic nerve. However, it is known that CCI leads to changes in skin temperature and that skin temperature can affect withdrawal latency. Aim of this study was to compare withdrawal latencies of constricted and contralateral hind limbs, to thermal stimulation, at the same artificially-induced skin temperatures. METHODS: Neuropathic pain was induced by four ligatures on the left sciatic nerve in adult male Wistar rats. Withdrawal latencies were measured from the 11th to 14th day after ligation, in different ambient temperatures, using the plantar test (Hargreaves method). By changing ambient we produced different hind limb skin temperatures. RESULTS: Our results show that (1) CCI cause an increase in skin temperature; (2) the withdrawal latency was inversely related to ambient and skin temperature in the same manner for both the ligated and contralateral hind limbs; and (3) withdrawal latencies did not differ significantly for the ligated and contralateral hind limbs when the temperature of the hind limbs was artificially made the same (i.e., by changing the ambient temperature). CONCLUSIONS: Withdrawal latencies to thermal stimulation did not differ on ligated and contralateral hind limb after CCI to the sciatic nerve if the temperature of the hind limbs was artificially or mathematically made the same. This finding may have significant impact on the interpretation results of neuropathic pain research.
Keywords: Animals; Wistar rats; konstrikce; nervus ischiadicus; Hyperalgesia; neuralgie; Rats, Wistar; Skin Temperature; Sciatic Nerve; Plantar test; CCI; Constriction; Temperature; hyperalgezie; Male; krysa rodu Rattus; Pain; Neuralgia; mužské pohlaví; zvířata; Rats; teplota kůže; potkani Wistar